2021
DOI: 10.1155/2021/3110622
|View full text |Cite|
|
Sign up to set email alerts
|

Second-Generation Tyrosine Kinase Inhibitor Discontinuation in Chronic Myeloid Leukemia Patients with Stable Deep Molecular Response: A Systematic Review and a Meta-Analysis

Abstract: The treatment with 2nd-generation tyrosine kinase inhibitors (2G-TKIs), namely, dasatinib and nilotinib, has been reported to have faster and deeper responses in newly diagnosed chronic phase-chronic myeloid leukemia (CP-CML) patients as compared with imatinab. A number of studies on the discontinuation of 2G-TKIs have been conducted and recently published. A meta-analysis was conducted in this study to assess the rate of treatment-free remission (TFR) rate as well as the long-term safety of 2G-TKI discontinua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Unfortunately, different criteria were applied in different studies for the TFR attempt qualification before the 2G-TKI discontinuation (MR4-MR4.5), and different definitions of molecular disease relapse (loss of MMR to loss of MR4.5) were applied. For these reasons, the interpretation of TFR rates at 24 months (ranging from 44 to 62.8 months) is difficult [50,[55][56][57][58][59].…”
Section: Current Results Of CML Treatmentmentioning
confidence: 99%
“…Unfortunately, different criteria were applied in different studies for the TFR attempt qualification before the 2G-TKI discontinuation (MR4-MR4.5), and different definitions of molecular disease relapse (loss of MMR to loss of MR4.5) were applied. For these reasons, the interpretation of TFR rates at 24 months (ranging from 44 to 62.8 months) is difficult [50,[55][56][57][58][59].…”
Section: Current Results Of CML Treatmentmentioning
confidence: 99%
“…A meta-analysis was conducted in patients with CML under a stable DMR to assess the prevalence of TFR and the long-term safety of discontinuation of second-generation TKIs therapy ( 67 ). Five single-armed, prospective cohort studies were included, and 517 patients were enrolled.…”
Section: Discontinuation Of Tkis Therapymentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%